Addressing COVID-19 “Ex catedra”: how religions in Russia and Belarus faced the pandemics - Khroul Victor (Studia Humanitatis, 2025)
The paper examines the strategies employed by religious institutions in Russia and Belarus during the on-going pandemic, analysing their arguments in official discourse and interactions with the governments. The results of the research indicate that, despite the stark contrast in governmental strategies for combating the pandemic (Russia’s approach being markedly stringent, while Belarus’ has been markedly lenient) shows how religions have called for compliance with government directives and have opposed conspiracy theories and dissident anti-vaccination activist movements. Minority religions also followed this approach. The necessity to conduct services online has provided a significant stimulus for the utilization of new digital technologies in predominantly conservative religious practices in both countries. The study revealed that the official documents under examination exhibited a clear predominance of theological elements over rational scientific elements in their argumentation. This finding highlights the inherent difficulties in the mediatisation of the Russian Orthodox Church narrative for the general public, which were already apparent but have become more pronounced during the pandemic.